ANALYSIS OF INTERNAL SOURCES OF HAZARDS IN CIVIL AIR OPERATIONS - Katarzyna CHRUZIK; Karolina WIŚNIEWSKA; Radosław FELLNER (Scientific Journal of Silesian University of Technology. Series Transport)
International air law imposes an obligation on the part of transport operators to operationalize risk management, and hence develop records of hazards and estimate the level of risk in the respective organization. Air transport is a complex system combining advanced technical systems, operators and procedures. Sources of hazards occur in all of these closely related and mutually interacting areas, which operate in highly dispersed spaces with a short time horizon. A highly important element of risk management is therefore to identify sources of danger, not only in terms of their own internal risks (the source of threats and activation of threats within the same transport organization), but also in the area of common risk (sources of threats beyond the transport system to which the activation of the hazard is related) and external risks (sources of threats outside the transport system). The overall risk management of a transport organization should consider all three risk areas. The paper presents an analysis of internal sources of threats to civil air operations and the resulting main risk areas. The article complements a previous paper by the same authors entitled “Analysis of external sources of hazards in civil air operations”.